Community Participation and its Correlation to Sustainable Development - Othman, Rasha Abdullah; Al-Qdah, Talal Abdel Karim (Journal of Humanities & Social Sciences, 2022)
The study aimed to identify the reality of community participation and its correlation to sustainable development in projects implemented by the Greater Amman Municipality, in cooperation with the German Agency for International Cooperation (GIZ), by identifying the interconnectedness of the community participation’s dimensions, namely: inclusion versus exclusion, change versus continuity, unity versus diversity, part versus all, to sustainable development.The study followed the descriptive analytical method due to its suitability to the nature of this study and the achievement of its objectives, and the researcher prepared a questionnaire consisting of (20) paragraph distributed to the study sample that consisted of 39 individuals distributed over the Nasr and Badr/Nazzal regions, who are beneficiaries of projects (ILCA) improving living conditions in disadvantaged area of Amman and (Cash for Work), and in view of the exceptional circumstances that Jordan and the whole world are witnessing due to the spread of the Corona epidemic, the questionnaire was distributed and communicated with members of the study sample through the electronic messaging program (whatsapp) in order to preserve the instructions of social distancing.The results of the study showed a positive correlation between inclusion versus exclusion, change versus continuity, unity versus diversity, part versus all, to sustainable development.In light of the study findings, a number of recommendations were presented, the most important of which is the need to work on a continuous change in the ideas put forward for projects development in a manner that contributes to the change in permanently reaching more services to the areas concerned with development, in addition to strengthening the role of the social worker as a link between the residents of the areas to be developed and the parties involved in the financing process.
Keywords: community participation; sustainable development; social worker